The future of swimming: "Myths and science" - Rushall, B.; Psy, R. (Swimming Science Bulletin, 2009)
A brief description of what are and are not acceptable knowledge criteria for swimming coaches is offered. Concern is expressed about the growing magnitude of belief-based coaching principles and advice which have the potential to depreciate coaching quality further. When information is limited to evidence-based research, a rich source of valid and reliable coaching knowledge is available. A sample of the implications of that knowledge is presented and covers the following topics: A physiological emphasis, altitude, lactate, pacing, whole-arm propulsion, and stretching/flexibility. Because of the dissonance between established opinions and the implications of data-based research, mixed reactions in the audience are expected.